Impact of human resources and organizational characteristics on public service standards for BPJS Health patients in Kupang City - Yohanes Ariyanto Seno; Apris Adu; Maria Magdalena Lino; Hendrik Toda (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to analyze the impact of human resources and organizational characteristics on the implementation of public service standards for BPJS Health patients at Prof. Dr. W.Z. Johannes General Hospital and Siloam Hospital in Kupang City. BPJS Health is Indonesia's national health insurance program, which provides universal health coverage to its citizens. Research Methodology: The research employs a mixed-methods approach, combining quantitative surveys with BPJS Health patients and qualitative interviews with hospital management and staff. Data were analyzed using statistical methods to compare service standards between the two hospitals and thematic analysis to explore underlying organizational factors. Results: The study identifies significant disparities in the application of public service standards between the two hospitals, influenced by differences in human resource competencies, organizational culture, and management practices. Key findings highlight challenges in service efficiency, patient satisfaction, and adherence to regulatory requirements. Conclusions: The research concludes that human resource quality and organizational characteristics critically shape the delivery of public health services. Strengthening competencies, improving management systems, and fostering a patient-centered culture are essential for enhancing service standards. Limitations: The study focuses on two hospitals in Kupang City Prof. Dr. W.Z. Johannes General Hospital and Siloam Hospital to compare public and private healthcare settings. However, limiting the sample to two institutions and relying on self-reported patient data may reduce generalizability and introduce potential bias. Contribution: This study contributes to public health management by emphasizing the role of human resources and organizational dynamics in achieving equitable and high-quality healthcare services. The findings offer actionable insights for policymakers and hospital administrators to optimize BPJS Health service delivery.